The phenotypic spectrum of fifty Czech m.3243A>G carriers - Dvorakova, V; Kolarova, H; Magner, M; Tesarova, M; Hansikova, H; Zeman, J; Honzik, T (Molecular genetics and metabolism, 2016)
BACKGROUND: Mitochondrial myopathy, Encephalopathy, Lactic Acidosis and Stroke-like episodes syndrome (MELAS) is a common mitochondrial disorder with varying multisystemic clinical manifestation. We present a comprehensive clinical picture of 50 Czech m.3243A>G carriers with emphasis on the sequence of symptoms in symptomatic patients. RESULTS: Symptoms developed in 33 patients (66%) and 17 carriers remained unaffected (34%). The age of onset varied from 1month to 47years of age, with juvenile presentation occurring in 53% of patients. Myopathy was the most common presenting symptom (18%), followed by CPEO/ptosis and hearing loss, with the latter also being the most common second symptom. Stroke-like episodes (SLE) occurred in fourteen patients, although never as a first symptom, and were frequently preceded by migraines (58%). Rhabdomyolysis developed in two patients. The second symptom appeared 5.0±8.3years (range 0-28years) after the first, and the interval between the second and third symptom was 2.0±6.0years (range 0-21years). Four of our patients remained monosymptomatic up to 12years of follow-up. The sequence of symptoms according to their time of manifestation was migraines, myopathy, seizures, CPEO/ptosis, SLE, hearing loss, and diabetes mellitus. The average age at death was 32.4±17.7years (range 9-60years) in the juvenile form and 44.0±12.7years (range 35-53years) in the adult form. Some patients with SLE harboured very low heteroplasmy levels in various tissues. No threshold for any organ dysfunction could be determined based on these levels. CONCLUSIONS: Sufficient knowledge of the timeline of the natural course of MELAS syndrome may improve the prediction and management of symptoms in patients with this mitochondrial disease.
Keywords: Infant; Humans; RNA, Transfer, Leu; kojenec; lidé středního věku; dítě; mitochondriální DNA; Child; Fully expressed phenotype; DNA, Mitochondrial; mutace; mladý dospělý; dospělí; Female; Phenotype; mitochondriální myopatie; lidé; syndrom MELAS; předškolní dítě; Adult; m.3243A>G; ženské pohlaví; Male; Middle Aged; RNA transferová Leu; fenotyp; Adolescent; Natural course; Czech Republic; Oligosymptomatic patients; Heteroplasmy; Heterozygote; Young Adult; MELAS Syndrome; Mitochondrial Myopathies; heterozygot; Mutation; Česká republika; mužské pohlaví; Child, Preschool; MELAS; mladiství